"Per viam rationis ... per legem vite": Pierre d'Ailly and the Last of the Fathers - Bellitto, Christopher M. (Cistercian studies quarterly, 2009)
The article discusses the views of theologian Pierre d'Ailly on Saint Bernard of Cellier de Clairvaux, Dijon, France. He describes Bernard as a paragon not only of a supremely honorable man but of someone who could speak truth to power. In his sermon "Sermo de beato Bernardo," he describes Bernard as a model figure and not the caricaturish anti-intellectual erroneously been labeled. He states that Bernard is a man who teaches as much by the example of his life as by his words.